2021
DOI: 10.3390/app11167326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Machine Learning Models for Estimating PM2.5 Concentrations across Malaysia

Abstract: Southeast Asia (SEA) is a hotspot region for atmospheric pollution and haze conditions, due to extensive forest, agricultural and peat fires. This study aims to estimate the PM2.5 concentrations across Malaysia using machine-learning (ML) models like Random Forest (RF) and Support Vector Regression (SVR), based on satellite AOD (aerosol optical depth) observations, ground measured air pollutants (NO2, SO2, CO, O3) and meteorological parameters (air temperature, relative humidity, wind speed and direction). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 150 publications
(191 reference statements)
3
11
0
1
Order By: Relevance
“…Zaman et al ( 2017 ) revealed that PM 2.5 concentration was 11.61 μg/m 3 in Malaysia, while in Delhi the value was 18.99 μg/m 3 as explored by Saraswat et al ( 2017 ). Also, Zaman et al ( 2021 ) found higher levels of PM 2.5 concentration across Malaysia during the dry season, which was quite consistent with the present research work. Abaset et al ( 2004 ) found that during the dry season, levels of PM 2.5 were 230.3 μg/m 3 for urban/industrial areas and 226.3 μg/m 3 for suburban zones, with a mean of 31.26 μg/m 3 and 26.38 μg/m 3 , respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Zaman et al ( 2017 ) revealed that PM 2.5 concentration was 11.61 μg/m 3 in Malaysia, while in Delhi the value was 18.99 μg/m 3 as explored by Saraswat et al ( 2017 ). Also, Zaman et al ( 2021 ) found higher levels of PM 2.5 concentration across Malaysia during the dry season, which was quite consistent with the present research work. Abaset et al ( 2004 ) found that during the dry season, levels of PM 2.5 were 230.3 μg/m 3 for urban/industrial areas and 226.3 μg/m 3 for suburban zones, with a mean of 31.26 μg/m 3 and 26.38 μg/m 3 , respectively.…”
Section: Discussionsupporting
confidence: 93%
“…A similar outcome was also obtained by Christakos et al ( 2018 ); Zhang et al ( 2021 ); and Lim et al ( 2019 ). The findings of Zaman et al ( 2021 ) are also consistent with the current result, with a cross-validation R 2 value of 0.84, a MAE of 10.07 μg/m 3 , and a lower RMSE value (12.1 μg/m 3 ). The findings of Shahriar et al ( 2020 ) represent that the R 2 values range between 0.66 and 0.78 and RMSE values range between 14.47 and 15.30 μg/m 3 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…RF validation worked somewhat better than SVR for spatial models, with statistical indicators of R 2 = 0.76, RMSE = 11.47 g for urban/industrial sites and R 2 = 0.64, RMSE = 10.76 for suburban/rural sites. The goal of this work is to predict PM 2.5 concentrations in Malaysia utilizing (ML) models derived from satellite AOD (aerosol optical depth) data, floor harmful emissions and weather parameters [5]. SVR calibration performed marginally better than RF calibration for the whole model, with R 2 = 0.69 and RMSE = 10.62 versus observed PM 2.5 concentrations.…”
Section: Approaches In Predicting Pmatter25 Using Regression Modelsmentioning
confidence: 99%
“…Despite the fact that countless studies on PM 2.5 have been conducted in various aspects and areas, PM 2. 5 has not yet been introduced into the data science sector.…”
Section: Approaches In Predicting Pmatter25 Using Regression Modelsmentioning
confidence: 99%